PENERAPAN GREENHOUSE HIDROPONIK TENAGA SURYA DAN PELATIHAN MANAJEMEN GUNA PENINGKATAN KAPASITAS USAHA KWT NANDUR SEDEKAH GUNUNGPATI SEMARANG TAHUN 2024 - Masdjojo, Gregorius Nasiansenus; Santosa, Agus Budi; Adhi, Antono (Jurnal Abdi Insani, 2024)
This Community Service was conducted at the Women's Farming Group (KWT) called Nandur Sedekah (NS) Gunungpati in Semarang City, Central Java. This group has gardening activities on empty land in the middle of settlements. The focus of their activities so far has been growing vegetables to support the needs of the members. Their activities have continued to develop until now, but along the way they have faced priority problems relating to production matters, governance matters, and sales matters. This service aims to provide solutions to the problems KWT is facing. The solution provided is in the form of building a Solar Hydroponic Greenhouse and Business Management and Digital Marketing Training. This service activity uses a process approach.  The process is; 1) Identifying problems by observing and interviewing KWT, 2) FGD determining priority problems, 3) Designing & developing a powered Hydroponic Greenhouse, and 4) Business Management and Digital Marketing Training. The results received by this group of service partners were the first to build a Solar Hydroponic Greenhouse. This building has the advantage of plastic material which is better at blocking sunlight, the capacity for planting vegetables in hydroponic pipes reaches 499 holes. Then, controlling the temperature, humidity, and watering time can be done via a web-based remote system automation. For the soft-skill aspect, it can be said that the management and several group cadre members also gained increased knowledge. The basic knowledge they receive is about business management and the application of digital marketing. Proof of changes in knowledge is carried out by comparing the results of the pre-test and post-test during training. More than 80% of training participants have experienced increased understanding. This PKM has overcome the KWT NS problem. The Solutions were taken through Solar Hydroponic Greenhouses and Business Management and Digital Marketing Training.